Fine Needle Aspiration (FNA) Cytology of Lymphoid Lesions; Definition and the Outcome of the Atypical/suspicious Diagnostic Category: Study of 34 Cases. - Emad Raddaoui (Journal of Hematology and Oncology Research, 2014)
Context: Fine needle aspiration cytology (FNA) is increasingly replacing excisional lymph node biopsy in the assessment of various lymphoid lesions. Recent changes in the classification of non-Hodgkin’s lymphoma, namely the WHO (World Health Organization) Classification of Tumors of Haematopoietic and Lymphoid Tissues has considerably expanded its classification of lymphomas based on the molecular and cytogenetic profiling and immunophenotyping. FNA diagnosis includes varied cytomorphologic diagnostic categories; one of them is the atypical/suspicious. Objective: The atypical/suspicious category constitutes about 20 % of all cases studied by FNA cytology. The objective of this study is to determine the definition and the outcome of this unique category. Design: A retrospective analysis of 34 fine needle aspirations with the diagnosis of atypical/suspicious cases were obtained during the period between 1995 –2000, and the histological and/or clinical follow-up was performed. Results: Flow cytometry was performed on all of the atypical/suspicious lesions. It was positive/diagnostic in 16 (47%) and negative in 18(53%) cases. Excisional follow-up biopsy was obtained in 30 cases. Of these 7(21%) confirmed to be negative, 17(50%) Non-Hodgkin’s lymphoma and 6 (18%) Hodgkin’s Lymphoma. Conclusion: The atypical/suspicious category by fine needle aspiration is a crucial diagnosis as it has proved to represent some type of lymphoma in about two third (68%) of cases.
Keywords: Fine Needle Aspiration